The Compensation of Pecuniary Damages in Wrongful Birth Cases - Morkūnaitė, Monika (Teisė, 2020)
This article examines the possibilities to recognise the compensation of the child’s maintenance cost in the wrongful birth cases. Both the foreign legal doctrine and case-law of foreign countries reveal different approaches to the possibility to allow such compensation. In such a context, taking into account the legal regulation, the perspectives of solution of this question in Lithuania are analysed.